Pengukuran Capability Level Sistem Informasi KKN Universitas Islam Negeri Sultan Syarif Kasim Riau menggunakan Framework COBIT 2019 - Dina Pani Safira; Rifsya Aulia; Megawati Megawati (Pusat Riset dan Inovasi Nasional, 2025)
Technology Information technology has an important role in supporting academic activities, including management of the KKN program. UIN Suska Riau has implemented the KKN Information System to facilitate student administration and monitoring. This research evaluates the effectiveness of the system using the COBIT 2019 framework, framework, focusing on domains APO07 (HR Management) and BAI01 (Program Management). Program). The evaluation results show that APO07 is at level 4 with an achievement of 77.99% (Largely Achieved), indicating that the process is structured but not fully optimized. but not yet fully optimized. While BAI01 reached level 5 with an achievement of 86.06% (Fully Achieved), indicating the process is sustainable and continues to be improved. to be improved. Based on these results, strategic recommendations were made to improve HR management and program effectiveness, to support more adaptive and aligned IT governance. IT governance that is more adaptive and aligned with institutional goals.